The legitimacy of sub-municipal councils in small and mid-sized cities under post-socialist conditions - Buček, Jan; Frassová, Mária (Quaestiones Geographicae, 2023)
Sub-municipal spatial community-based bodies, represented in the form of councils, have important roles in urban governance in many countries. This paper attempts to contribute to a better understanding of the legitimacy of sub-municipal councils (SMCs) in the specific conditions of small and mid-sized cities, within the context of democratising post-socialist society and decentralising government. Using the questionnaire and additional local resources, we discuss a selected set of relevant components of the legitimacy of SMCs, such as the traditions of their existence, legal and democratic grounds, autonomy, personal qualities, expertise, procedural issues, results and stability. We document these issues pertaining to the case of SMCs in small and medium-sized cities in Slovakia, emphasising the need for more components of legitimacy for their stable existence, with the strong impact of local traditions, legal framework development and incorporation into local representative democracy bodies.